Annotation and in silico localization of the Affymetrix GeneChip Porcine Genome array - Naraballobh W. (2014)
Expression microarrays including the Affymetrix GeneChip Porcine Genome Arrays are valuable tools for studying genes and functional networks relevant for the expression of complex traits and the responsiveness of the organism to various treatments. An updated annotation and, for the first time, localization on the porcine physical genome map of »Affymetrix GeneChip Porcine Genome Array probe sets was made through a workflow of 3 pipelines of comparisions addressing various NCBI (National Center for Biotechnology Information) and EnsEMBL (Ensembl project) databases. »BLAST« (Basic Local Alignment Search Tool) comparisons of Affymetrix probe set consensus sequences with the EnsEMBL Sscrofa 9 cDNA database provided 23 799 probe sets with hits. After annotation 19730 gene symbols were obtained using the data management system BioMart. Comparison of the Affymetrix probe set consensus sequences with the porcine genome sequence (EnsEMBL Sscrofa 9 LatestGP database) revealed 23 298 probe sets with BLAST hits. In the third pipeline in addition to EnsEMBL Sscrofa 9 cDNA and genomic sequence databases also human, mouse and pig NCBI reference sequence RNA databases were interrogated in an integrated approach where also a threshold of bit score >50 or >90% identity over >100 bp was applied in order to filter questionable annotations and localizations. Gene symbols and gene names were queried from HGNC (human genome organization (HUGO) gene nomenclature committee), EASE (EASE: the Expression Analysis Systematic Explorer) and Entrez Gene revealing 20 269 annotated probe sets. 20 467 probe sets were in silico mapped addressing various sources: EnsEMBL Sscrofa 9 LatestGP, pre-EnsEMBL Sscrofa 8.52 LatestGP, NCBI pig reference sequence RNA and genomic databases and PigQTLdb (Pig Quantitative Trait Locus [QTL] database). Using the new annotation and localization data in functional genomics studies will facilitate improving the understanding of the control of quantitative traits in pigs.